Elaborate expressions in Dai Lue - Hanna, William J. (2024)
The Dai Lue language, in common with other Southeast Asian languages, has many elaborate expressions: four-syllable units that often have idiomatic and colourful meanings. Using data from a corpus of Dai Lue texts, this paper explains seven strategies that are used for creating elaborate expressions. These range from those that are flexible and open to creative manipulation, to those that form fixed lexemes. The most flexible strategy, and the most common, is based on the large number of coordinate compound words in Dai Lue. Coordinate compounds are expanded upon in several ways to form a four-syllable expression. Other strategies involve reduplication and the heaping up of synonyms. Elaborate expressions that are lexemes are distinguished from those that are not. Listing of elaborate expressions based on their canonical structure has proved to be a dead end typologically. An exploration of these seven formation strategies in Southeast Asian languages holds promise for new insights into their morphology.